Sex Equitable Prehospital Stroke Triage Using Symptom Severity and Teleconsultation - Wiebert, Elin; Berglund, Annika; Sjöstrand, Christina; Eriksson, Einar E.; Mazya, Michael V. (Frontiers in Neurology, 2021)
Objectives: We aimed to determine whether there are sex differences in prehospital accuracy of the Stockholm Stroke Triage System (SSTS) to predict large artery occlusion (LAO) stroke, and endovascular thrombectomy (EVT), and whether clinical characteristics differ between men and women undergoing “code stroke” ambulance transport. Materials and Methods: This prospective observational study collected data between October 2017 and October 2018. We included 2,905 patients, transported as “code stroke,” by nurse-staffed ground ambulance, to a Stockholm Region hospital. Exclusion criteria were private or helicopter transport, onset outside Stockholm, and in-hospital stroke. We compared overall accuracy, sensitivity, specificity, positive and negative predictive values, and clinical characteristics between sexes. Results: No significant sex differences in SSTS predictive performance for LAO or EVT were found, overall accuracy for LAO 87.3% in women vs. 86.7% in men. Women were median 4 years older and more frequently had stroke mimics (46.2 vs. 41.8%). Women more commonly had decreased level of consciousness (14.0 vs. 10.2%) and moderate-to-severe motor symptoms (by 2.7–3.8 percentage points), and less commonly limb ataxia (7.2 vs. 9.7%). Conclusions: The SSTS had equal predictive performance for LAO and EVT among men and women, despite minor sex differences in the clinical characteristics in patients undergoing ambulance transport for suspected stroke.